(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This story introduces readers to the daily life of the people from Ometepe Island, who, faithful to the legends of their ancestors, kept everything they were told as a divine word. Ometepe, belongs to the department of Rivas, Nicaragua and is considered one of the seven wonders of the world for the beauty of its beaches, flora, fauna and its cultural richness. The island also has two active volcanoes (El Concepción and El Maderas), one of fire and the other of water; Islets and lagoons that make its splendor stand out even more, among them the asonado Charco Verde. Likewise, the text tells us one of the legends that is most relevant on the island and that has spread to some departments of Nicaragua because many have abandoned their lands in search of new life opportunities. In addition, this work gives richness and recreation to the legend that is naturally known, allowing it to be located in the time and place where the events took place.